Interorganizational cooperation and supplier performance in high-technology supply chains. Issue 3 (March 2020) - Connor, Neale O'; Lowry, Paul Benjamin; Treiblmaier, Horst
Abstract: Never in history have global supply-chain relationships in high-tech electronics firms been more sophisticated, complicated, and almost always tied in some major aspect to China. This research examines how interorganizational (IO) cooperation impacts performance and what role relationship learning and information technology (IT) integration play in the value-creation process for Chinese suppliers in business-to-business (B2B) supply chains. We examine this issue using data collected from face-to-face interviews with supply chain managers and executives from 1, 004 Chinese high-tech electronic component suppliers. The results strongly support the hypothesis that IO cooperation improves a supplier's performance regarding both its major customer and overall marketplace. Relationship learning and IT integration are important mediating variables that drive performance. The strongest effect in our study was the influence of IO cooperation on relationship learning. A unique aspect of this study is that it focuses on a large sample of a specific supplier type—high-tech Chinese suppliers. This, combined with the fact that the sampled companies were involved in manufacturing 13 different product groups, greatly increases the generalizability of the results. Abstract : Supply chain performance; Buyer-supplier relationships; Relationship marketing theory; Social exchange theory; Collaboration; Electronics industry; Global supply chain, Business; Globalization; Operations management; Technology adoption; Technology management